The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-879x2006005000192
|View full text |Cite
|
Sign up to set email alerts
|

Connections: can the 20th century coronary heart disease epidemic reveal something about the 1918 influenza lethality?

Abstract: This essay proposes that the ecologic association shown between the 20th century coronary heart disease epidemic and the 1918 influenza pandemic could shed light on the mechanism associated with the high lethality of the latter. It suggests that an autoimmune interference at the apoB-LDL interface could explain both hypercholesterolemia and inflammation (through interference with the cellular metabolism of arachidonic acid). Autoimmune inflammation, then, would explain the 1950s-60s acute coronary events (coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Interestingly using a mouse model of atherosclerosis (Apolipoprotein E deficient mouse) injection of influenza A virus into the mice was associated with significant infiltration of inflammatory and smooth muscle cells in atherosclerotic plaques, superficial platelet aggregation, and occasional subocclusive fibrin thrombus [43], which may in part provide an explanation for the increase in cardiovascular deaths seen during influenza epidemics [44]. Interestingly, a cohort association exists between rates of vulnerability to influenza deaths in 1918 and CHD mortality among survivors from those vulnerable birth cohorts [45]. These researchers suggest that the 1918 influenza pandemic may have played a role in the future development of CHD in the survivors, through an effect secondary to the influenza priming of 1918 vulnerable individuals for late development of CHD potentially through mechanisms of endothelial dysfunction and lipid dysregulation.…”
Section: Influenza and Coronary Heart Diseasementioning
confidence: 99%
“…Interestingly using a mouse model of atherosclerosis (Apolipoprotein E deficient mouse) injection of influenza A virus into the mice was associated with significant infiltration of inflammatory and smooth muscle cells in atherosclerotic plaques, superficial platelet aggregation, and occasional subocclusive fibrin thrombus [43], which may in part provide an explanation for the increase in cardiovascular deaths seen during influenza epidemics [44]. Interestingly, a cohort association exists between rates of vulnerability to influenza deaths in 1918 and CHD mortality among survivors from those vulnerable birth cohorts [45]. These researchers suggest that the 1918 influenza pandemic may have played a role in the future development of CHD in the survivors, through an effect secondary to the influenza priming of 1918 vulnerable individuals for late development of CHD potentially through mechanisms of endothelial dysfunction and lipid dysregulation.…”
Section: Influenza and Coronary Heart Diseasementioning
confidence: 99%
“…Azambuja [4] suggested that the high pathogenicity of the (H1) influenza virus among young adults in 1918-1919 might have re-sulted from an immune response that went awry, in birth-cohorts originally primed by the influenza viruses emerging during the 1888-1890 Pandemic (according to sero-epidemiologic studies, possibly an H3 virus [5]). In 2009, severe cases and deaths have spared individuals born before 1957 (oldest than 60) [6][7][8], concentrating among those born in years of greater H3 (post-1968) and H2?…”
Section: Antecedentsmentioning
confidence: 99%
“…In addition, morbidity and mortality associated with influenza infections may manifest as a decompensation of underlying chronic cardio‐pulmonary conditions leading to increased mortality 2 . It has previously been demonstrated that both influenza and other viral respiratory infections may cause an inflammatory state capable of destabilizing atherosclerotic plaques which in turn lead to fatal cardiovascular events 14–18 . Therefore, in this paper we have included medical diagnosis other than ‘ deaths attributable to respiratory infections’ to evaluate the impact on mortality of influenza and RSV.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has previously been demonstrated that both influenza and other viral respiratory infections may cause an inflammatory state capable of destabilizing atherosclerotic plaques which in turn lead to fatal cardiovascular events. [14][15][16][17][18] Therefore, in this paper we have included medical diagnosis other than 'deaths attributable to respiratory infections' to evaluate the impact on mortality of influenza and RSV. The Centers for Disease Control and Prevention estimate that seasonal influenza viruses cause an average of 51 203 deaths per year in the United States, whereas RSV is thought to cause an average of 17 358 deaths per year.…”
Section: Introductionmentioning
confidence: 99%